Deterministic Assembly of Single Sub‐20 nm Functional Nanoparticles Using a Thermally Modified Template with a Scanning Nanoprobe. Issue 52 (12th November 2020) - Meng, Yan; Cheng, Gang; Man, Zaiqin; Xu, Ya; Zhou, Shuang; Bian, Jie; Lu, Zhenda; Zhang, Weihua
Abstract: A deterministic assembly technique for single sub‐20 nm functional nanoparticles is developed based on nanostructured templates fabricated by hot scanning nanoprobes. With this technique, single nanoparticles including quantum dots, polystyrene fluorescent nanobeads, and gold nanoparticles are successfully assembled into 2D arrays with high yields. Experimental and theoretical analyses show that the key for the high yields is the hot‐probe‐based template fabrication technique, which creates geometrical nanotraps and modifies their surface energy simultaneously. In addition to single nanoparticle patterning, further experiments demonstrate that this technique is also capable of building complex nanostructures, such as nanoparticle clusters with well‐defined shapes and heterogeneously integrated nanostructures consisting of quantum dots and silver nanowires. It opens the door to many important applications. Abstract : A deterministic assembly technique for single sub‐20 nm functional nanoparticles is developed based on nanostructured templates fabricated by hot scanning nanoprobes. With this technique, single nanoparticles including quantum dots, polystyrene fluorescent nanobeads, and gold nanoparticles are successfully assembled into 2D arrays with high yields. Additionally, complex nanostructures, such as nanoparticle clusters and heterogeneously integrated nanostructures, are realized.